2015
DOI: 10.1182/blood-2015-01-624833
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane TNF-α preferentially expressed by leukemia stem cells and blasts is a potent target for antibody therapy

Abstract: Key Points tmTNF-α expressed on LSC and leukemia cells correlates with poor risk stratification and adverse clinical parameters. Targeting tmTNF-α by monoclonal antibody eradicates LSC and blasts, preventing leukemia regeneration in secondary transplant in NOD-SCID mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 32 publications
5
34
0
Order By: Relevance
“…[13] In line with this report, we found that transmembrane TNF-α expression was up-regulated in gemcitabine and paclitaxel treated PDAC cells when compared to untreated PDAC cells. In the next step, we sought to understand if the combination of anti-TNF-α treatments will synergize with chemotherapy in killing PDAC cells.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…[13] In line with this report, we found that transmembrane TNF-α expression was up-regulated in gemcitabine and paclitaxel treated PDAC cells when compared to untreated PDAC cells. In the next step, we sought to understand if the combination of anti-TNF-α treatments will synergize with chemotherapy in killing PDAC cells.…”
Section: Discussionsupporting
confidence: 86%
“…Anti-TNF-α antibodies have shown therapeutic benefits on various pre-clinical cancer models including orthotopic PDAC pre-clinical model. [1317] However, the clinical and targeting values of TNF-α in PDAC, chemotherapy synergistic effects, and underlying anti-PDAC mechanisms of anti-TNF-α treatments remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We could identify 94 gene products and 47 molecular pathways that had close to 1 AUC scores for the ALL-normal comparison (Supplementary dataset S4, Table 1). Among those, branches of Akt signaling [24], cAMP [25], cytoplasmic and mitochondrial apoptosis [26], PTEN [27], ATM checkpoint [28], Hedgehog [29], HGF [30], GSK3 [31], Estrogen and Glucocorticoid reception [32, 33], IGF1R [34], IL2 [35], TNF [36], ILK [37], JAK-STAT [38], JNK [39], mTOR [40], TGF-beta [41], Ras [42], PPAR [43], NGF [44], VEGF [45], Wnt [46], HIF1 and Notch signaling [47] were previously reported in the literature as ALL-associated pathways. However, the identified GPCR and TRAF-associated apoptosis marker pathways were new, thus representing ~4% of the total ALL-specific pathways.…”
Section: Resultsmentioning
confidence: 99%
“…The transcription factor Atonal homolog 1 (Atoh1) protein, stabilized by TNF-α, could enrich colon CSCs, and induce high malignant potential (34). In myeloid leukemia, TNF-α secreted by the CSCs could promote NFκB pathway/p65 pathway and support stem cells survival (35,36). Similarly, TNF-α induces NFκB pathway activation to protect colorectal CSCs from death, and induce tumor regression (37).…”
Section: Interplay Between Inflammatory Tumor Microenvironment and Camentioning
confidence: 99%